Healthcare Workers in South Korea Maintain a SARS-CoV-2 Antibody Response Six Months After Receiving a Second Dose of the BNT162b2 mRNA Vaccine - Choi, Jae Hong; Kim, Young Ree; Heo, Sang Taek; Oh, Hyunjoo; Kim, Misun; Lee, Hyang Ran; Yoo, Jeong Rae (Frontiers in Immunology, 2022)
Background: Effective vaccines against coronavirus disease 2019 (COVID-19) are available worldwide; however, the longevity of vaccine effectiveness is not known. Objective: We performed a prospective observational study to assess the antibody response of healthcare workers against severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) after BNT162b2 mRNA COVID-19 vaccination. Methods: SARS-CoV-2 neutralizing antibody (nAb) and spike (S) protein-IgG (S-IgG) antibody titers were examined in participants who received two doses of the BNT162b2 mRNA COVID-19 vaccine in a single center between March 1, 2021, and October 11, 2021. Antibody levels were analyzed at four times: before vaccination (visit 1), 4 weeks after the first vaccination (visit 2), 3 months after the second vaccination (visit 3), and 6 months after the second vaccination (visit 4). Results: A total of 249 healthcare workers at Jeju National University Hospital were enrolled in this study, and 982 blood samples were analyzed. The mean age was 38.1 ± 9.5 years, and 145 (58.2%) participants were females. Positive nAbs (inhibition rates ≥ 20%) were measured in 166/249 (66.7%) subjects at visit 2, 237/243 (97.5%) subjects at visit 3, and 150/237 (63.3%) subjects at visit 4. A S-IgG (≥50 AU/mL) positivity was detected in 246/249 (98.8%) subjects at visit 1, and all participants had positive S-IgG antibody levels at visits 3 and 4 after being fully vaccinated. Further analysis of S-IgG levels revealed a median quantitative antibody level of 1275.1 AU/mL (interquartile range [IQR] 755.5–2119.0) at visit 2, 2765.9 AU/mL (IQR 1809.8–4138.4) at visit 3, and 970.1 AU/mL (IQR 606.0–1495.9) at visit 4. Considering the change in antibody levels over time, both nAb and S-IgG levels at visit 4 decreased compared with the corresponding levels at visit 3. No evidence of SARS-CoV-2 infection was found among any of the participants throughout the study. Conclusions: The BNT162b2 mRNA vaccine was effective in protecting healthcare personnel working in COVID-19-related departments. While the level of S-IgG antibodies was maintained for 6 months after the second vaccination, nAb levels waned over this 6-month period, indicating the need for a booster vaccination in some healthcare workers 6 months after full vaccination.